To block or not to block: European approaches to content regulation, and implications for freedom of expression [2-s2.0-77955598996] - Akdeniz, Y. (My University, 2010)
Based on the limited effectiveness of state laws, and lack of harmonization at international level a number of states started to introduce policies to block access to Internet content and websites deemed illegal which are situated outside their legal jurisdiction. However, blocking policies are not always subject to due process principles, decisions are not necessarily taken by the courts of law, and often administrative bodies or Internet hotlines run by the private sector decide which content or website should be subject to blocking. Therefore, increasingly, the compatibility of blocking action is questioned with regards to the fundamental right of freedom of expression. This article assesses significant developments at the pan-European level with regards to the development, and implementation of Internet content blocking policies. Adaptation of content blocking policies from certain member states of both the European Union and the Council of Europe will be used to assess the nature and implementation of access blocking policies. It will be argued that there could be a breach of Article 10 of the European Convention on Human Rights if blocking measures or filtering tools are used at state level to silence politically motivated speech on the Internet. © 2010 Xiaolu Zhang. Published by Elsevier Ltd. Allrights reserved.
Keywords: Access Blocking; Censorship; Filters; Freedom Of Expression; Hotlines; Illegal And Harmful Content; Internet Content Regulation; Notice And Take Down; Access Blocking; Censorship; Filters; Freedom Of Expression; Hotlines; Illegal And Harmful Content; Internet Content Regulation; Notice And Take Down; Crime; Laws And Legislation; World Wide Web; Internet